Deciphering the mechanism of Huang-Lian-Jie-Du-Decoction on the treatment of sepsis by formula decomposition and metabolomics: Enhancement of cholinergic pathways and inhibition of HMGB-1/TLR4/NF-κB signaling. (July 2017) - Xu, Dingqiao; Lv, Yan; Wang, Junsong; Yang, Minghua; Kong, Lingyi
Graphical abstract: Abstract: Sepsis is the major cause of morbidity and mortality in surgical patients. Huang-Lian-Jie-Du-Decoction (HLJDD), a well-known Chinese herb formula, has long been used for the treatment of sepsis. In this investigation, by leaving one herb out each time, the four component herbs of HLJDD were reformulated to four HLJDD variants Form1-4, corresponding to the removal of Phellodendri Chinensis Cortex, Scutellariae Radix, Gardeniae Fructu and Coptidis Rhizoma, respectively. Metabolomics approach combined with histological inspection, biochemical measurement and molecular biology was used to investigate the treatment effects of HLJDD and its four variants on cecal ligation and puncture (CLP) model of sepsis, which were compared to decipher the formulating principles of HLJDD. Our results showed that HLJDD exhibit the strongest therapeutic effects in the CLP models as compared with the four variants, which could be ascribed to its most significant enhancement of cholinergic anti-inflammatory pathway and inhibition of HMGB-1/TLR4/NF-κB signaling pathway. Most of all, metabolites changed specifically between groups of HLJDD and its four variants were related with the exceptional treatment effects of HLJDD.